ChemInform Abstract: Reaction of 4‐Hydroxycoumarin with 2‐Acetyloxiranes. Issue 16 (22nd April 2014) - Os'kina, I. A.; Tikhonov, A. Ya.; Bagryanskaya, I. Yu.; Gatilov, Yu. V.; Fedorova, O. S.
Abstract Reaction of 4‐hydroxycoumarin (I) with 2‐acetyloxiranes [(II) or (IV), resp.] leads to the compound (III) or the corresponding dehydration product (V), respectively.